A Comparison of Postoperative Analgesic Effect of Intravenous Tramadol versus Transdermal Buprenorphine Patch in Patients Undergoing Aortofemoral Graft Surgery - Meena, Reema; Sharma, Ashish; Garg, Namita; Yadav, Ramgopal (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: The popularity of the transdermal buprenorphine patch (TDB) is currently increasing for chronic pain management because of its ease of use, non-invasive nature, sustained drug delivery, and avoidance of side effects associated with oral or parenteral routes. However, its role in postoperative pain management for aortofemoral bypass surgery is poorly established. The study was designed to compare the postoperative analgesic effect of intravenous tramadol versus transdermal buprenorphine patch in patients undergoing aortofemoral graft surgery. Objective: To compare the efficacy between a buprenorphine patch versus intravenous tramadol for postoperative analgesia in patients undergoing aortofemoral bypass surgeries.  Methods: This is a hospital-based, prospective, randomized, and interventional study. This study was conducted in the cardiac surgery Operation Theatre (OT). A total of 60 patients of either sex belonging to ASA 2 or 3 in the age group of 30-60 years and BMI ≤ 40 kg/m2 scheduled for aortofemoral bypass surgery were enrolled in this study. These 60 patients were divided into two groups; the intravenous tramadol and the transdermal buprenorphine patch group using a randomization table. Results: The two groups were comparable in terms of demographical data, duration of surgery, and time for extubation. The analysis of variance showed that the VAS score was higher in the buprenorphine group as compared to the tramadol group for the first 3 hours post operatively but after that, the VAS score was significantly less in the buprenorphine group at various study intervals. A greater number of patients complained of pain for the first 3 hours postoperatively, but after that the patients had better pain relief for the rest of the study period. Conclusion: Transdermal buprenorphine applied preoperatively is a safe and effective option for postoperative pain management as it offers superior pain control and reduces the need for rescue analgesia, thereby decreasing potential side effects as compared to intravenous tramadol.